Past Gaming Experience and Cognition as Selective Predictors of Novel Game Learning Across Different Gaming Genres - Smith, Evan T.; Bhaskar, Bhargavi; Hinerman, Alex; Basak, Chandramallika (Frontiers in Psychology, 2020)
Past experience with video-games and cognitive abilities have been hypothesized to independently facilitate a greater ability to learn new video games and other complex tasks. The present study was conducted to examine this “learning to learn” hypothesis. We examined the predictive effects of gaming habits (e.g., self-identification as a “Gamer”, hours spent gaming per week, weekly gaming frequency, relative preference for strategy over action games) and cognitive abilities (short-term memory, working memory and processing speed) on learning of two novel videogames in 107 participants (aged 17-77 years). One videogame was from action genre, and the other was from strategy genre. Hours spent gaming per week and working memory were found to specifically predict learning of the novel strategy videogame, after controlling for the effects of age, gender and action game learning. In contrast, self-identification as a “Gamer” was the only specific significant predictor of action game learning, after controlling for the effects of age, gender and strategy game learning. Age of the participant negatively impacted learning of both games; however the pattern of the predictive relationships on both action and strategy game learnings were not moderated by age. Importantly, preference for action versus strategy game genre had no differential effects on learning of the two novel games, nor were there any gender differences in identification as a gamer or genre preference. Findings from this study suggest that while past gaming experience and cognition do appear to influence the learning of novel video games, these effects are selective to the game genre studied, and is not as broad of an effect as the “learning to learn” model suggests.